What Factors Determine the Online Consumer Behavior in This Digitalized World? A Systematic Literature - Muluken Ayalew; Shimelis Zewdie (Human Behavior and Emerging Technologies)
This review study envisioned to address the basic objective that is to investigate determinants of online consumer behavior. A conventional review strategy was used to address the objective raised above, i.e., systematic strategy, and also, the obtained data were analyzed via content analysis. In addition to the above, the study also employed descriptive research design to present the obtained result descriptively. According to the generated findings, purchase intention is the most studied area, which is followed by adoption, and conversely, continuance or repurchase stage of online consumer behavior is the most underresearched area. Perceived usefulness, perceived risk, attitude, perceived ease of use, trust, social influence, subjective norms, perceived enjoyment, security, perceived behavioral control, web design quality, privacy and security concerns, demographic factors (e.g., age, gender, occupation, education, and income), perceived value, service quality, perceived satisfaction, psychological factors (e.g., relative advantage), facilitating conditions, and consumers’ experience are the most influential factors significantly affecting online consumer behavior at large. Therefore, it is advised that industries those are experienced or newcomers in the market to work on the identified factors determining the online consumer behavior, to sustain and achieve success in this dynamic world.